2019
DOI: 10.1080/10717544.2019.1676843
|View full text |Cite
|
Sign up to set email alerts
|

Dual functional matrix metalloproteinase-responsive curcumin-loaded nanoparticles for tumor-targeted treatment

Abstract: The limitations of anticancer drugs, including poor tumor targeting and weak uptake efficiency, are important factors affecting tumor therapy. According to characteristics of the tumor microenvironment, in this study, we aimed to synthesize matrix metalloproteinase (MMP)-responsive curcumin (Cur)-loaded nanoparticles (Cur-P-NPs) based on amphiphilic block copolymer (MePEG-peptide-PET-PCL) with MMP-cleavable peptide (GPLGIAGQ) and penetrating peptide (r9), modified to improve tumor targeting and cellular uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…As the DOX concentration increased (40–80 μg/mL), (DOX + CUR)-FA-NPs and (DOX + CUR)-NPs showed better anti-proliferative abilities than (DOX + CUR). In this phase, as the drug content increased, more (DOX + CUR)-loaded nanocarriers were taken up into the cells because of an increased cell-uptake efficiency (Guo et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the DOX concentration increased (40–80 μg/mL), (DOX + CUR)-FA-NPs and (DOX + CUR)-NPs showed better anti-proliferative abilities than (DOX + CUR). In this phase, as the drug content increased, more (DOX + CUR)-loaded nanocarriers were taken up into the cells because of an increased cell-uptake efficiency (Guo et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the emergence of MDR (by the P-gp pathway; Li et al, 2018 ), strong cell toxicity, and poor targeting selection have seriously hindered its clinical application. Curcumin (CUR) is a low-toxicity natural drug made of polyphenols extracted from Zingiberaceae plants (Wu et al, 2019 ) and is less effective against cancer than first-line chemotherapy but has broad-spectrum effects (Guo et al, 2018 ; Zhang et al, 2018 ; Barati et al, 2019 ; Guo et al, 2019 , 2020 ). Hou et al ( 2019 ) and Lv et al ( 2016 ) have shown that CUR is an excellent P-gp inhibitor that effectively maintains a high DOX concentration in drug-resistant human breast cancer MCF-7/ADR cells.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo pharmacokinetics demonstrated that CUR-P-NPs are more targeted to MCF-7 xenografts than normal tissues, causing significant increase in bioavailability. 156…”
Section: Camptothecinmentioning
confidence: 99%
“…In another recent study, the tumour‐targeting mechanism and the effect of the cellular uptake of MMP‐reactive CUR NPs on the breast cancer cell line MCF‐7 were analysed in vivo and in vitro, respectively. In vivo pharmacokinetics demonstrated that CUR‐P‐NPs are more targeted to MCF‐7 xenografts than normal tissues, causing significant increase in bioavailability 156 …”
Section: Cpps and Anti‐cancer Cargoes Deliverymentioning
confidence: 99%
“…To address these problems, an increasing numbers of studies are focusing on how to enhance the tolerance of curcumin, improve the targeting of curcumin delivery, overcome low bioavailability and obtain better therapeutic effects (124,125). A variety of nano-curcumin formulations have been introduced, which have improved the anti-cancer effects of curcumin (126,127). It is considered that curcumin will serve a more important role in the prevention and treatment of cancer in the future.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%